Pola mobilitas pedagang angkringan Di kota ponorogo (mobility pattern of the angkringan vendors In ponorogo city) - Santoso Slamet; Jusuf Harsono (Universitas Mercu Buana Yogyakarta, 2013)
The goal of this research for knowing mobility pattern of the angkringan vendor group in Ponorogo City. The location research is in the Ponorogo District. For getting data we used Depth Interview and Observation Methodes. We used purposive sampling method to decide the informan. For analyzing th data we used Inductive-Interpretative-Konseptualization. The result of the research is that the mobility pattern of the angkringan vendors in Ponorogo City have many forms: 1) Horizontal mobility, that is migration of the angkringan vendors from the original town (most from Central Java) to Ponorogo City, East Java; 2) Vertical mobility, that is the increasing of the social-economical status of the angkringan vendors family.